(untitled) (Configurazioni. Research on contemporary poetry, 2023)
This paper introduces the proceedings of the Fourth Annual Seminar on Contemporary Poetry, held at the University of Perugia on 10-11 November 2022 and dedicated to legitimation apparatus. Building on some excerpts of the introduction to the anthology Il pubblico della poesia (1975) signed by Alfonso Berardinelli, I propose a theoretical examination of the concepts of apparatus and legitimation, aimed at highlighting their pragmatic and negotiated nature. The poetry of the present (and of the past) appears more understandable by dropping an essentialist approach, based on the a priori of value, and instead opening up to the plural diversity of practices. A brief review of the five contributions collected in the proceedings follows.